Synthesis and Aggregation of Polymer‐Amyloid β Conjugates. Issue 1 (21st October 2019) - Evgrafova, Zhanna; Rothemund, Sven; Voigt, Bruno; Hause, Gerd; Balbach, Jochen; Binder, Wolfgang H.
Abstract: Modulating the assembly of medically relevant peptides and proteins via macromolecular engineering is an important step in modifying their overall pathological effects. The synthesis of polymer–peptide conjugates composed of the amyloidogenic Alzheimer peptide, Aβ1‐40, and poly(oligo(ethylene glycol)m acrylates) ( m = 2, 3) with different molecular weights ( M n = 1400–6600 g mol −1 ) is presented here. The challenging conjugation of a synthetic polymer to an in situ aggregating protein is established via two different coupling strategies, only successful for polymers with molecular weights not exceeding 6600 g mol −1, relying on resin‐based synthesis or solution‐based coupling chemistries. The conjugates are characterized by high‐performance liquid chromatography and matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry. The aggregation of these polymer‐Aβ1‐40 conjugates, as monitored via thioflavine‐T (ThT)‐fluorescence spectroscopy, is accelerated mainly upon attaching the polymers. However, the appearance of the observed fibrils is different from those composed of native Aβ1‐40, specifically with respect to length and morphology of the obtained aggregates. Instead of long, unbranched fibrils characteristic for Aβ1‐40, bundles of short aggregates are observed for the conjugates. Finally, the ThT kinetics and morphologies of Aβ1‐40 fibrils formed in the presence of the conjugates give some mechanistic insights. Abstract : Modulating the assembly of proteins via macromolecular engineering is an important step in modifying their overall pathological effects. The challenging conjugation of the aggregating amyloidogenic Alzheimer peptide, Aβ1‐40, to poly(oligo(ethylene glycol)m acrylates) ( m = 2, 3) is reported. Fibrillation of the conjugates displays fibrils different in length and morphology compared to native Aβ1‐40 .